Contextual Learning of Character Values in Minangkabau Culture Course to Strengthen National Identity - Zulfa, Zulfa (Journal of Moral and Civic Education, 2019)
Current problems in various regions make the world of higher education think of doing many things. The most pressing problems now are Lesbian, Gay, Bisexual and Transgender (LGBT), which is increasingly troubling, drugs and other immoral acts that are increasingly worrying about the world of higher education. This is the problem that makes education in Indonesia focus on the character field. One program that can strengthen the national identity in higher education in learning Minangkabau Culture. The purpose of this study is to apply Contextual Learning (CTL) in learning character values ​​in Minangkabau culture and strengthen the national identity of students. The method used in writing is a literature study, the author tries to develop a contextual learning model which is examined from various relevant references. The results of this study were to use CTL learning to provide independence for students to identify character values ​​derived from the values ​​of life in the family environment or in the community in the Minangkabau community. Besides this learning model instills character values ​​directly through habituation that applies in Minangkabau cultural customs by participating in community activities, including collaborative activities or community meetings that are able to foster a character of tolerance and cooperation. Through CTL in learning Minangkabau Culture that contains character values ​​found in the family or Minangkabau community that can be a reinforcement of national identity. Keywords: contextual learning, character values, identity and Minangkabau culture ABSTRAK Permasalahan yang terjadi saat ini di berbagai daerah membuat dunia pendidikan tinggi berpikir untuk melakukan banyak hal. Masalah yang paling mendesak saat ini adalah Lesbian, Gay, Biseksual dan Transgender (LGBT), yang semakin meresahkan, obat-obatan dan tindakan amoral lainnya yang semakin mengkhawatirkan dunia pendidikan tinggi. Inilah masalah yang membuat pendidikan di Indonesia fokus pada bidang karakter. Salah satu program yang dapat menjadikan penguatan dalam identitas kebangsaan dalam pendidikan tinggi pada pembelajaran Budaya Minangkabau. Tujuan dari penelitian ini adalah untuk menerapkan pembelajaran kontekstual (Contextual Learning/CTL) dalam pembelajaran nilai-nilai karakter dalam budaya Minangkabau serta memperkuat identitas nasional mahasiswa. Metode yang digunakan dalam penulisan adalah studi literatur, penulis mencoba mengembangkan model pembelajaran kontekstual yang ditelaah dari berbagai referensi yang relevan. Hasil dari penelitian ini adalah menggunakan pembelajaran CTL untuk memberikan kemandirian bagi mahasiswa untuk mengidentifikasi nilai-nilai karakter yang berasal dari nilai-nilai kehidupan di lingkungan keluarga atau di masyarakat dalam masyarakat Minangkabau. Selain itu model pembelajaran ini menanamkan nilai karakter secara langsung melalui pembiasaan yang berlaku dalam adat budaya Minangkabau dengan berpartisipasi dalam kegiatan masyarakat, termasuk kegiatan kerja sama atau pertemuan warga yang mampu menumbuhkan karakter toleransi dan kerja sama. Melalui CTL dalam pembelajaran Budaya Minangkabau yang berisi nilai-nilai karakter yang ditemukan dalam keluarga atau masyarakat Minangkabau yang dapat menjadi penguat identitas bangsa. Kata kunci: pembelajaran kontekstual, nilai karakter, identitas dan budaya Minangkabau